Soap opera viewing in a communal context - Michele Tager (Communicare)
This paper presents some of the findings of an ethnographic audience study of the soap opera viewing patterns and interpretations of Zulu-speaking students living in residences at a South African university (Natal University’s Durban campus) who watch The Bold and the Beautiful (an American soap opera) and Generations (a South African soap opera). Although the research undertaken covered various aspects of the soap opera viewing experience and the consumption of an international vs a local soap opera, this paper will focus specifically on the nature of the viewing process and the ways in which the respondents relate to both soap operas, and it touches briefly on how the viewing patterns of the students and their motivations for watching compare with audience studies conducted elsewhere in the world.